2021
DOI: 10.1039/d1ta03064g
|View full text |Cite
|
Sign up to set email alerts
|

Dual crosslinked metallopolymers using orthogonal metal complexes as rewritable shape-memory polymers

Abstract: This work presents the synthesis and characterization of easily tuneable shape-memory metallopolymers. Furthermore, the structural design enables excellent rewriting properties. For this purpose, two different polymers were synthesized using either...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…Inspired by such elegant designs, Guan and co-workers have incorporated weak supramolecular bonds, based on metal–ligand coordination or hydrogen bonds, into the polyacrylate arms of a comb structure with a polystyrene backbone. , The microphase separation of the low glass-transition temperature ( T g ) arm from the high- T g backbone yields high mechanical strength originating from the dispersed hard phase and fast healing by the reversible dissociation of transient bonds within the soft phase . This approach has recently been further expanded by employing orthogonal combinations of more defined transient bonds, even from different natures, but with significantly different lifetimes. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by such elegant designs, Guan and co-workers have incorporated weak supramolecular bonds, based on metal–ligand coordination or hydrogen bonds, into the polyacrylate arms of a comb structure with a polystyrene backbone. , The microphase separation of the low glass-transition temperature ( T g ) arm from the high- T g backbone yields high mechanical strength originating from the dispersed hard phase and fast healing by the reversible dissociation of transient bonds within the soft phase . This approach has recently been further expanded by employing orthogonal combinations of more defined transient bonds, even from different natures, but with significantly different lifetimes. …”
Section: Introductionmentioning
confidence: 99%
“…Among all of the transient bonds used, metal–ligand complexes are widely employed for the development of biomimetic transient hydrogels, not only because they can be formed simply in water but since their strength and stability can be freely tuned over several orders of magnitude by a mere change of the metal ion, its oxidation state, and the selection from the extensive library of ligands. As such, the necessary coexistence of two relaxation modes with significantly different lifetimes to achieve self-healing can be realized simply by employing two different metal ions or two various ligands. ,, In this regard, pyridinedicarboxamide (PDCA) is a unique tridentate ligand that is reported to form two distinct coordination bonds with significantly different dynamics upon complexation with the Fe 3+ ion. Therefore, it has been widely integrated into different polymer chemistries and has shown promising self-healing properties. , Despite the acceptable individual performance, it has also been utilized in combination with carboxylate-based ligands, which are also capable of complexation with the Fe 3+ ion, and have shown synergistic properties. , The small-molecule variant of the PDCA ligand has shown a remarkable pH-sensitive complexation with covalent bond-like stability under basic conditions, which is a characteristic of protic ligands . Nevertheless, there is no information on the kinetics, thermodynamics, and pH responsivity of PDCA complexes, which otherwise could be employed to expand their utility as novel building blocks for metallo-supramolecular polymer networks.…”
Section: Introductionmentioning
confidence: 99%
“…23,38 In previous works, we already presented several examples for the utilization of metal ligand interactions for shape-memory applications, both as switching unit and as stable phase, or for the preparation of self-healing materials. 39,40 The motivation for this study was to (i) achieve a simplication of the synthesis of fully metal-complex-based shapememory polymers and (ii) to create an intelligent material that combines both self-healing and shape-memory abilities. The synthesis is enabled by the mixing of two linear, ligandbearing polymers, each containing a different ligand.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 It has been shown that such shape memory effects (SMEs) are associated with other chemical and physical properties of SMPs, such as the molecular architecture, glass transition and stretchability. [17][18][19][20][21][22][23][24][25][26][27] By optimizing the molecular architecture of SMPs, it is accessible to adjust the temperature for shape programming and shape recovery and the deformability during shape programming (i.e., the maximum strain (e m ) could be achieved). However, in sharp contrast, research studies on the controllability of the shape recoverability (i.e., recovery rate (R r ) and recovery velocity (V r )) of SMPs have rarely been reported, which were the essential parameters to characterize the shape memory performance of SMPs as well.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 It has been shown that such shape memory effects (SMEs) are associated with other chemical and physical properties of SMPs, such as the molecular architecture, glass transition and stretchability. 17–27 By optimizing the molecular architecture of SMPs, it is accessible to adjust the temperature for shape programming and shape recovery and the deformability during shape programming ( i.e. , the maximum strain ( ε m ) could be achieved).…”
Section: Introductionmentioning
confidence: 99%